Analisis Miskonsepsi Kemampuan Literasi Numerasi terhadap Pemahaman Konsep FPB dan KPK pada Siswa Kelas IV Sekolah Dasar - Puspitasari, Ratna; Srinana Wardani, Imas; Ladyawati, Erlin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the forms of students' misconceptions in understanding the concept of Greatest Common Factor (FPB) and Least Common Multiple (KPK) when viewed from the perspective of numeracy literacy skills. This study uses a qualitative approach with a case study design. The research subjects consisted of six fourth-grade elementary school students who were selected purposively based on the categories of high, medium, and low ability. Data collection techniques were carried out through essay tests based on numeracy literacy and semi-structured interviews. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Data validity was tested through triangulation of techniques, sources, and time. The results showed that students with high ability did not experience significant misconceptions, but were still weak in providing conceptual explanations. Students with medium ability experienced conceptual and procedural misconceptions, especially in determining the use of FPB and KPK. Meanwhile, students with low ability experienced conceptual, procedural, and representational misconceptions. These findings indicate that numeracy literacy skills play an important role in minimizing mathematical misunderstandings in elementary school students.